THE RELATIONSHIP OF DIABETES MELLITUS AND HYPERTENSION WITH MORTALITY IN COVID-19 PATIENTS - Yasmin Nihayatun Nadzifah; Atik Choirul Hidajah (Universitas Airlangga, 2022)
Background: Coronavirus disease 2019 (COVID-19) can infect the human respiratory system and causes 6.93% of all deaths in East Java Province. Comorbid diabetes mellitus and hypertension can exacerbate COVID-19 patients. Purpose: This study aims to analyze the relationship between diabetes mellitus and hypertension with mortality in COVID-19 Patients in Lamongan District. Methods: This study used an analytic observational study with a cross-sectional design. The study population was patients diagnosed with COVID-19 and registered at Lamongan District Health Office from April to August 2020, as many as 412 patients. The study sample was 93 patients who were taken by simple random sampling. The dependent variable in the study was the incident of mortality in COVID-19 patients. The independent variables in the study were gender, age, hypertension, and diabetes mellitus. Data analysis was using the chi-square test. Results: The variables studied that had a relationship with mortality in COVID-19 patients were age ≥ 60 years (p = 0.02; PR = 3.23; 95% CI = 1.29 <PR <8.10) and diabetes mellitus (p = 0.03; PR = 3.20; 95% CI = 1.23 <PR <8.36). The variables studied that did not have a relationship with mortality in COVID-19 patients were gender (p = 0.30; PR = 1.72; 95% CI = 0.74 <PR <4.03) and hypertension (p = 0.72; PR = 1.37; 95% CI = 0.34 <PR <5.48). Conclusion: Age and diabetes mellitus are significantly associated with mortality in COVID-19 patients, but sex and hypertension are not significantly associated with mortality in COVID-19 patients.